2017
DOI: 10.1093/ee/nvx158
|View full text |Cite|
|
Sign up to set email alerts
|

Phenology of the Potato Psyllid, Bactericera cockerelli (Hemiptera: Triozidae), and “Candidatus Liberibacter solanacearum” in Commercial Potato Fields in Idaho

Abstract: Zebra chip disease (ZC) is an emerging disease of potato in which tubers are produced with striped necrotic patterns that make them unmarketable. ZC is associated with the bacterium "Candidatus Liberibacter solanacearum" (Lso), which is transmitted by the potato psyllid, Bactericera cockerelli (Šulc; Hemiptera: Triozidae). First found in Idaho during 2011, ZC now contributes to increased production costs each season via additional insecticide sprays. To clarify the extent and severity of the threat of ZC in Id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 34 publications
0
32
0
Order By: Relevance
“…Means within a column followed by the same letter are not significantly different based on pairwise comparisons and 95% confidence levels abundance typically is very low early during the season, increasing considerably around the time of harvest (Munyaneza et al 2009;Rondon 2012;Wenninger et al 2017). Similar phenologies have been reported in Texas (Goolsby et al 2007;Workneh et al 2014) and New Zealand (Cameron et al 2009).…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Means within a column followed by the same letter are not significantly different based on pairwise comparisons and 95% confidence levels abundance typically is very low early during the season, increasing considerably around the time of harvest (Munyaneza et al 2009;Rondon 2012;Wenninger et al 2017). Similar phenologies have been reported in Texas (Goolsby et al 2007;Workneh et al 2014) and New Zealand (Cameron et al 2009).…”
Section: Discussionmentioning
confidence: 53%
“…Plants were replaced as needed. The presence of Lso in potato psyllids was determined by Polymerase Chain Reaction (PCR) using methods described by Wenninger et al (2017). The Lso status of the colonies was regularly tested and typically ranged from 80 to 100%.…”
Section: To 2015 Field Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of Lso in B. cockerelli was determined by Polymerase Chain Reaction (PCR). The details of the analysis are presented in Munyaneza et al [4], Wenninger et al [21], Workneh et al [17], and Harrison et al [28]. The percentage of adult B. cockerelli testing positive for Lso was determined as the ratio of the number of B. cockerelli positive for Lso to the total number of collected B. cockerelli during each week of the monitoring period of each year.…”
Section: Methodsmentioning
confidence: 99%
“…The results of the present study corroborate with the finding of Antolínez et al [33] who reported the arrival of potato psyllid in the potato fields when the average air temperature is greater than 15 • C and the peak population occurred when air temperature was about 25 • C in Spain. Wenninger et al [21] also correlated the population abundance of adults B. cockerelli with the accumulated thermal unit and found the population peak at 1775 • C in late August in the Treasure Valley and at 1498 • C in the Magic Valley in Idaho. Lewis et al [34] suggested integrating accumulated thermal units into the management and control of B. cockerelli and proposed a model that integrates thermal unit to simulate the development of potato psyllid infestation.…”
Section: Bactericera Cockerelli Infection By Zebra Chip Pathogen (Canmentioning
confidence: 99%